Model-Independent reconstruction of the expansion history of the universe from type Ia supernovae - Benítez Herrera, Sandra; Bartelmann, Matthias (Arxiv, 2011)
Based on the largest homogeneously reduced set of Type Ia supernova luminosity data currently available -- the Union2 sample -- we reconstruct the expansion history of the Universe in a model-independent approach. Our method tests the geometry of the Universe directly without reverting to any assumptions made on its energy content. This allows us to constrain Dark Energy models and non-standard cosmologies in a straightforward way. The applicability of the presented method is not restricted to testing cosmological models. It can be a valuable tool for pointing out systematic errors hidden in the supernova data and planning future Type Ia supernova cosmology campaigns.
Gesehen am 22.09.2017